Direct selling for dummies - Ellsworth, Belinda (--For dummies., 2015)
This guide is for anyone involved or interested in direct sales. It teaches you everything you need to know to achieve and maintain lasting success, including insider tips, how to structure your business and your time, and how to leverage your customer relationships to optimize sales and achieve your goals.